A longitudinal behavioral analysis of aquarium whale sharks (Rhincodon typus): insights into anticipatory cues, individual variation, and social interaction - Gallimore, Connor G.; Walton, Celeste; Nugent, Richard; Fradkin, Maury; Poppell, Laurie; Schreiber, Christian; Coco, Christopher; Grober, Matthew; Carlson, Bruce; Dove, Alistair D. M.; Black, Michael P. (Frontiers in Marine Science, 2024)
Rhincodon typus, or the whale shark, is the largest extant fish in the world and is classified as endangered on the IUCN’s Red List. Due to their enormous size and conservation status, whale sharks are rarely housed in aquaria. Here we present a behavioral analysis culminating from a large effort by 89 observers from 2008–2012 to study four R. typus (ID codes: AL, TA, TR, YU) longitudinally in an aquarium setting. We found that relatively simple behavioral metrics such as swim speed, depth occupation, swimming direction, and lead-follow interactions demonstrated R. typus individual variation and responses to habitat changes. All sharks displayed increased swim speeds 30-minutes before regimented feed times, when there was scent of food being fed to other animals in the habitat. Consistently in the habitat, one male shark (YU) was recorded swimming more at depth, faster, almost exclusively clockwise, and engaged in fewer close proximity interactions with others than expected by chance. In contrast, a larger female shark (AL) was observed swimming the slowest, at the surface more than others, led other sharks more than she followed, and had strong lead-follow interactions with another shark of the opposite sex (TA). TA and TR did not differ from each other in depth profiles or speed, but did differ in their proclivity to lead or follow. Depth preferences and lead-follow interactions suggest some partitioning of the habitat and the possibility of social hierarchy in this species. These results represent the first longitudinal behavioral analysis of aquarium R. typus, offering meaningful similarities and contrasts to field observations.